2001
DOI: 10.1038/sj.jhh.1001165
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide and hypertension: not just an endothelium derived relaxing factor!

Abstract: The importance of endothelial nitric oxide (NO) generation in sustaining a tonic systemic vasodilatation is well established. Inhibiting NO production produces hypertension in animals and in humans and not surprisingly there has been considerable interest in establishing whether deficiencies of endothelial NO pathway activity are implicated in the aetiology of essential hypertension. The results of these investigations have been inconsistent with some suggestion that observed deficiencies of both basal and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
32
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 93 publications
1
32
0
3
Order By: Relevance
“…2,11 Indeed, several studies have demonstrated that low NO, whose circulating levels are considered as a surrogate of endothelial dysfunction, is an early marker in patients with common cardiovascular risk factors, such as diabetes, smoking and hypertension. 2 In a recent issue of the Journal of Human Hypertension, Srivastava et al 12 confirm that in patients with essential hypertension, NO is significantly lower than in healthy controls and that smoking habit markedly decreases NO production. The authors also examined the role of vascular cell adhesion molecule (VCAM)-1 and E-selectin, as well as the relationship between those and systolic blood pressure (SBP) and/or diastolic blood pressure (DBP).…”
Section: No Is Produced By Endothelial Cells Via Nos III (Enos) or Vimentioning
confidence: 99%
See 4 more Smart Citations
“…2,11 Indeed, several studies have demonstrated that low NO, whose circulating levels are considered as a surrogate of endothelial dysfunction, is an early marker in patients with common cardiovascular risk factors, such as diabetes, smoking and hypertension. 2 In a recent issue of the Journal of Human Hypertension, Srivastava et al 12 confirm that in patients with essential hypertension, NO is significantly lower than in healthy controls and that smoking habit markedly decreases NO production. The authors also examined the role of vascular cell adhesion molecule (VCAM)-1 and E-selectin, as well as the relationship between those and systolic blood pressure (SBP) and/or diastolic blood pressure (DBP).…”
Section: No Is Produced By Endothelial Cells Via Nos III (Enos) or Vimentioning
confidence: 99%
“…2 Of note, endothelial dysfunction in hypertension may occur very early, even in white coat hypertension. 13 Another aspect of this complexity emerges from the therapeutic targeting of endothelium impairment.…”
Section: No Is Produced By Endothelial Cells Via Nos III (Enos) or Vimentioning
confidence: 99%
See 3 more Smart Citations